Russian cardiological clinical trials - S. N. Tolpygina; S. A. Shalnova; S. Yu. Martsevich; N. V. Kiseleva (Кардиоваскулярная терапия и профилактика)
An attempt has been made to systematize the data on Russian cardiological clinical trials, included in the first edition of the reference book “Russian clinical and epidemiological studies in cardiology”. Design, duration, sample size, study population and other characteristics are described for these studies (n=93). The majority of the Russian studies are relatively short (approximately 70% are under 1 year), and the sample size is relatively small (approximately 50% include <500 subjects). The limited duration and size do not allow assessing therapy effects on hard end-points, such as all-cause mortality, cardiovascular mortality, and incidence of major cardiovascular events as prognostic markers. Therefore, most of the studies use surrogate end-points with lower prognostic value. The results of the current analysis demonstrate that not all the Russian studies comply with the good clinical practice standards. Only 31% of the published studies were prospective, and 40% claimed to be randomised, however, in many publications, there was no detailed description of randomisation procedure or randomisation quality control. However, some studies were methodologically robust. As an example, a cohort, prospective, noncomparative study “PROGNOSIS of coronary heart disease (CHD)” is presented. The description of this study will be included in the next edition of the reference book.